The Study of Consumption Pattern and Hospitalization Costs of Elderly Covered by Iran Health Insurance Organization - Shokrollah Zandi; Abolghasem Pourreza; Sedigheh Salavati (Kerman University of Medical Sciences, 2016)
Introduction:Health policymakers faced with new challenges such as increasing elderly population. This study aimed to investigate the consumption pattern and hospitalization costs of the elderly covered by Iran Health Insurance Organization in teaching hospitals of Sanandaj, Iran. Method:In this descriptive-analytical as a cross sectional one, the samples included 5753 elderly covered by Iran Health Insurance Organization who used hospitalization services in three teaching hospitals of Sanandaj in 2013. Using Chi square and t-test, data analysis was performed. Results:The frequency of elderly hospitalizations was 6703 cases. Mean of hospitalization rate was 1.04 times in men and 1.36 times in women. The elderly hospitalization costs were about 27.8% of the total hospitalization costs. The costs of hospitalization services were statistically different between elderly and non-elderly patients except the rehabilitation services. Although there was statistically significant relationship between the age of elders and their length of stay but no statistically significant relationship between elderly's age and their hospitalization costs was reported. In addition, no significant difference between the mean costs of each hospitalization in men and women was reported. Conclusion: It was concluded that the hospitalization costs are higher in elderly patients compared to the non-elderly patients, so managers and policymakers are required to have a program for funding the elderly's health services costs. Considering the evidences in aged economic area including consumption patterns and services costs seems to be necessary. Keywords: Elderly, Hospitalization Services, Consumption Pattern, Costs, Teaching Hospital Citation: Zandi S, Pourreza A, Salavati S.The Study of Consumption Pattern and Hospitalization Costs of Elderly Covered by Iran Health Insurance Organization. Journal of Health Based Research 2016; 2(1): 15-27.